Impact of physical and enzymatic cell wall opening on the release of pre-gelatinized starch and viscosity forming potential of potato flakes. (15th August 2018) - Reyniers, S.; De Brier, N.; Matthijs, S.; Brijs, K.; Delcour, J.A.
Highlights: Potato flakes (PFs) are used as ingredient in different food systems. Swelling power and mean particle size determine PF instant viscosity development. Short extracellular amylose molecules improve PF gelation upon cooling. Physical or enzymatic cell wall opening enhance PF swelling and release of starch. Cell wall opening improves the PF instant viscosity development and gelation. Abstract: Potato flakes (PFs) are used in instant foods. They contain pre-gelatinized starch which readily develops viscosity upon hydration. We here provide the first report on factors influencing their viscosifying potential. Swelling power (SP) (r = 0.719, p < 0.01) and mean particle size (r = −0.704, p < 0.05) mainly determine instant viscosity development of PF suspensions while short extractable extracellular amylose molecules [degree of polymerization between 150 and 1500 (EE-AM150-1500 )] positively impact their cold paste viscosity (CPV) (r = 0.717, p < 0.01) in Rapid Visco Analyzer (RVA) models. Cell wall opening by ball milling or cellulase treatments increased PF SP resulting in up to 75% higher RVA peak viscosity readings. Furthermore, the release of EE-AM150-1500 molecules increased CPV by about 30% since they readily associated upon cooling. Partial cell wall opening thus improves the viscosifying potential of PFs and expands their applicability in instant foods.